(untitled) (Bangladesh Journal of Public Administration, 2021)
This study presented an overview of Bangladesh’s tourism sector, which also strived to identify the opportunities and challenges that warrant policy interventions. Both primary and secondary data were used in this research. It was found that the frequency of inbound tourists’ arrival showed a declining trend. The tourism sector’s growth cannot keep pace with national growth domestic product though Bangladesh’s global rank and score showed an increasing trend. Despite economic upsurging and vast potentiality, Bangladesh could not be a popular destination for foreign tourists. Cultural and natural resources and tourist and airport infrastructure have been identified as the disadvantaged pillars. The country cannot offer cheaper and more comfortable accommodation and transportation facilities. There is a lack of diversity in tourism events and fun-making elements. Online tourist platforms, booking, and financial transactions are not widely available and accessible. Supermall and safe food providing agencies have not been developed across the country. The study advocates for formulating a holistic national tourism policy eyeing achieving sustainable development goals. There is ample scope for developing a regional tourism hub taking Bhutan and Nepal.